2012
DOI: 10.1016/j.puhe.2011.09.027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for injury in a national cohort of 87,134 Thai adults

Abstract: SummaryBackgroundInformation is needed regarding risk factors associated with injury. In middle- and lower-income countries, injury studies have focused on road traffic injuries and less attention has been given to other types of injuries.MethodsThis study is part of overarching health–risk transition research in Thailand with a large national cohort study that began in 2005 (n = 87,134). Associations between potential determinants and overall injury were measured, as well as injury by location (transport, hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
31
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 35 publications
11
31
2
Order By: Relevance
“…Industrial Health 2013, 51, [34][35][36][37][38][39][40][41][42][43][44][45][46] As expected from other studies, we found a higher risk of serious occupational injury among males 30,31) . Another important risk factor significantly associated with occupational injury was low income (≤7,000 Baht/month), already noted with a previous study of the Thai cohort on risk factors associated with injury 26) . As with other studies on occupational injury, we found that the risk of injury related to job type, rural job location 32) , and frequency of alcohol consumption 33) .…”
Section: Compare With Other Studiessupporting
confidence: 68%
See 2 more Smart Citations
“…Industrial Health 2013, 51, [34][35][36][37][38][39][40][41][42][43][44][45][46] As expected from other studies, we found a higher risk of serious occupational injury among males 30,31) . Another important risk factor significantly associated with occupational injury was low income (≤7,000 Baht/month), already noted with a previous study of the Thai cohort on risk factors associated with injury 26) . As with other studies on occupational injury, we found that the risk of injury related to job type, rural job location 32) , and frequency of alcohol consumption 33) .…”
Section: Compare With Other Studiessupporting
confidence: 68%
“…The heat stress and the occupational injury questions were in different sections of the questionnaire so answers on these issues were independent of each other. The distribution and frequency of risk factors associated with non-traffic injuries by locations have been reported in two recent studies using baseline TCS data 25,26) .…”
Section: Data and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Bad or less favorable health conditions potentially increase the risk of more severe injury. (28) The results of our multivariate analysis showed that severity of injury due to motorcycles was higher as compared with severity due to other land transportation after adjustment for sex and age. Injury due to motorcycles had a 1.3-fold more severe (OR=1.3;95% CI: 1.1-1.6) and a 1.1-fold higher adjusted odds ratio (AOR=1.1;95% CI 1.0-1.3) as compared with with the odds ratios for other land transportation after adjustment for sex and age.…”
Section: Discussionmentioning
confidence: 74%
“…Oral health is one example where age is important, with older cohort members having a much higher prevalence of poor oral health, which is then associated with poor quality of life (Yiengprugsawan et al, 2011b(Yiengprugsawan et al, , 2011c. Around 8.5 per cent of cohort members had trouble with their hearing (Yiengprugsawan et al, 2012e), and one-third of the cohort had vision impairment (Yiengprugsawan et al, 2012f). Both of these problems were strongly associated with poor self-rated health and psychological distress.…”
Section: Key Research Findingsmentioning
confidence: 99%